Analisis Kepuasan Konsumen Terhadap Sabun Cair Virgin Coconut Oil (VCO) Dari Penjual Citra Ayu: Studi Kasus Di Platform Belanja Online Shopee - Biamnasi , Ambrosius Trikurniawan; Wrasiati, Luh Putu; Yoga , I Wayan Gede Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
The development of e-commerce has transformed consumer behavior, including the purchase of personal care products such as Virgin Coconut Oil (VCO) liquid soap. This study aims to analyze the product and service quality attributes affecting consumer satisfaction with VCO liquid soap sold by Citra Ayu on the Shopee platform. The research employs a survey method using Importance-Performance Analysis (IPA) and Customer Satisfaction Index (CSI) approaches. Data were collected through questionnaires distributed to consumers. The CSI indicates a high level of satisfaction, with scores of 86.68% for product quality and 86.58% for service quality, both categorized as “very satisfied.” Regarding product quality, the most important attributes are raw material quality with an importance level of 4.52, product fragrance with a score of 4.40, and price suitability with product quality scoring 4.38. However, product effectiveness needs improvement, as it has a performance index (TKI) of 99.22%. For service quality, cleanliness and neatness of packaging, timely delivery, and responsiveness to customer complaints are key factors with importance scores of 4.38 and 4.36. The packaging design attribute has the highest performance level at 108.44%, while seller knowledge about the product has the lowest at 96.80%. Citra Ayu has successfully provided high consumer satisfaction through good product and service quality. Nevertheless, improvements in product effectiveness and seller knowledge are necessary to maintain competitiveness in the e-commerce market.